The burden of cardiovascular disease in the elderly: morbidity, mortality, and costs - Yazdanyar, Ali; Newman, Anne B (Clinics in geriatric medicine, 2009)
Cardiovascular disease (CVD) in older Americans imposes a huge burden in mortality, morbidity, disability, functional decline, and health care costs. In light of the projected growth of the population of older adults over the next several decades, the societal burden attributable to CVD will continue to rise. There is thus an enormous opportunity to foster successful aging and to increase functional life years through expanded efforts aimed at CVD prevention. This article provides an overview of the epidemiology of CVD in older adults, including an assessment of the impact of CVD on mortality, morbidity, and health care costs.